Complement Anaphylatoxins and Inflammatory Cytokines as Prognostic Markers for COVID-19 Severity and In-Hospital Mortality - Alosaimi, Bandar; Mubarak, Ayman; Hamed, Maaweya E.; Almutairi, Abdullah Z.; Alrashed, Ahmed A.; AlJuryyan, Abdullah; Enani, Mushira; Alenzi, Faris Q.; Alturaiki, Wael (Frontiers in Immunology, 2021)
COVID-19 severity due to innate immunity dysregulation accounts for prolonged hospitalization, critical complications, and mortality. Severe SARS-CoV-2 infections involve the complement pathway activation for cytokine storm development. Nevertheless, the role of complement in COVID-19 immunopathology, complement‐modulating treatment strategies against COVID-19, and the complement and SARS‐CoV‐2 interaction with clinical disease outcomes remain elusive. This study investigated the potential changes in complement signaling, and the associated inflammatory mediators, in mild-to-critical COVID-19 patients and their clinical outcomes. A total of 53 patients infected with SARS-CoV-2 were enrolled in the study (26 critical and 27 mild cases), and additional 18 healthy control patients were also included. Complement proteins and inflammatory cytokines and chemokines were measured in the sera of patients with COVID-19 as well as healthy controls by specific enzyme-linked immunosorbent assay. C3a, C5a, and factor P (properdin), as well as interleukin (IL)-1β, IL-6, IL-8, tumor necrosis factor (TNF)-α, and IgM antibody levels, were higher in critical COVID-19 patients compared to mild COVID-19 patients. Additionally, compared to the mild COVID-19 patients, factor I and C4-BP levels were significantly decreased in the critical COVID-19 patients. Meanwhile, RANTES levels were significantly higher in the mild patients compared to critical patients. Furthermore, the critical COVID-19 intra-group analysis showed significantly higher C5a, C3a, and factor P levels in the critical COVID-19 non-survival group than in the survival group. Additionally, IL-1β, IL-6, and IL-8 were significantly upregulated in the critical COVID-19 non-survival group compared to the survival group. Finally, C5a, C3a, factor P, and serum IL-1β, IL-6, and IL-8 levels positively correlated with critical COVID-19 in-hospital deaths. These findings highlight the potential prognostic utility of the complement system for predicting COVID-19 severity and mortality while suggesting that complement anaphylatoxins and inflammatory cytokines are potential treatment targets against COVID-19.